Analisis Kesalahan Penggunaan Huruf Kapital dan Tanda Baca pada Karangan Deskripsi terhadap Keterampilan Menulis Siswa Kelas 5 SD - Purmini, Purmini; Azhar, Arry Ptriasurya; Yenni, Yenni (Lembaga Yasin AlSys, 2023)
The purpose of this study was to find out errors in the use pf capital letters and punctuation in descriptive essays on the writing skills of 5th graders at Amanah Elementary School, Tangerang City. The type of research method used by the researcher is description. The reason the uses a qualitative approach is because the presentation of data and data analysis will be delivered in the form of a sentence description based on the results of tests, interview, and documentation studies. The results of the study found 23 students’ writings that had been analyzed there were 69 errors in the use of capital letters in the first letter of the beginning of the sentence, there are 19 errors in using capital letters in the first letter of people’s names, errors in the use of capital letters in the first letter of the name of the year, month and big day or holiday there are 7 errors, there are 16 errors in the use of capital letters in the first letter of the geographic names. And in the results of the analysis of errors in the use of punctuation, there are 57 errors in the use of punctuation point, 8 errors in the use punctuation marks, 6 errors in the use of hyphens.